(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
In the era of the Fourth Industrial Revolution, companies are required to adapt and innovate to remain competitive by leveraging digital technologies, automation, and the integration of intelligent systems that significantly transform business paradigms. Technological innovation is one of the key success factors for companies to compete in the global market. This article aims to analyze technological innovation strategies that companies can adopt to navigate the dynamics of modern industry, including the Internet of Things (IoT), big data analytics, artificial intelligence (AI), cloud computing, and automation-based technologies. By integrating these technologies into their business models, companies can enhance competitiveness, improve product quality and services, and accelerate decision-making processes. Descriptive qualitative methods were chosen using secondary data sourced from various literature, such as books, articles, and home pages, to access relevant information.